Design factors for a successful Shared Space Street (SSS) design - Jayakody, Ranmalsingha R. J. C.; Keraminiyage, Kaushal; Alston, Mark; Dias, Nuwan (International Journal of Strategic Property Management, 2018)
The concept of Shared Space Street (SSS) has the potential to bring many benefits to a city. Those include promotion of social interaction, the connectivity within the city for both vehicles and pedestrians, active engagement of the people with the space, walkability, vitality and street livability, better economic wealth and alike. These factors work together to improve livability, vitality of street and indirectly bring economic wealth to municipalities through increasing the footfall to shops, enhancing the health and safety of the locality and increasing the property values. Hence, this clearly is a consideration for strategic property management and relevant professionals. This concept has also been criticized for its practical issues when implemented in some parts of the world. Such issues include difficulties faced by aged people and people with disabilities, harassments faced by the cyclists, etc. This paper explores the methods and approaches that can be used to harness potential advantages of the SSS concept and to overcome its practical issues and criticisms through a detail evaluation of design driven use of space in three case studies within United Kingdom. Finally, this paper proposes a set of design factors which can be applied to a SSS design in order to ensure a successful implementation.